Stakeholders' enactment of competing logics in IT governance: polarization, compromise or synthesis?. Issue 4 (4th July 2018) - Boonstra, Albert; Yeliz Eseryel, U.; van Offenbeek, Marjolein A. G.
Abstract: Governing IT while incorporating stakeholders with diverse institutional backgrounds remains a challenge. Stakeholder groups are typically socialized differently and may have different perspectives on IT governance dilemmas. Yet, extant literature offers only limited insight on socialized views on IT governance. This study uses an institutional logics lens to examine how competing institutional logics get connected in IT governance practices through dominant stakeholders' enactment patterns and how these enactment patterns may affect the organization's IT performance. We find that logics were coupled to the three dominant stakeholder groups, but only loosely so. Congruence between the three logics they enacted depended on the IT governance dilemma at hand. Our findings demonstrate how within a triad of competing logics, switching rivalry among hybrid logics may develop. Here, the enactments led to two hybrid logics, none of which became dominant. Remarkably, the IT professionalism logic accommodated polarization between medical professionalism and the managerial logic, causing unstable IT governance. We propose that IT professionalism offers room for agency and is crucial in determining the resulting enactment patterns: polarizing, compromising or even synthesizing. This study may raise managers' awareness of the competing logics underlying IT governance practices and clarify the pivotal role of IT professionalism in IT governance debates.